Whole-Earth Decompression Dynamics: New Earth Formation Geoscience Paradigm Fundamental Basis of Geology and Geophysics - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2021)
Policymakers and educators depend upon the advice of scientists to warn of natural and anthropogenic dangers to the environment and to Earth’s biota. Decades of mal-administered government-funding have led to the corruption of science, however, and to the formation of unofficial cartels that promulgate a seriously flawed, consensus view of Earth’s origins, structure, and geodynamic behavior. Proponents of this “consensus” view, in contradiction to long-standing scientific principles, suppress or ignore concepts that better explain Earth’s fundamental behavior. Here I present, as published in the peer-reviewed scientific literature over a period of four decades, a fundamentally new, indivisible paradigm that posits Earth’s early formation as a Jupiter-like gas giant, which makes it possible to derive virtually all the geological and geodynamic behavior of our planet, including two previously unanticipated, powerful endogenous energy sources; the origin of mountain ranges characterized by folding; the origin and typography of ocean floors and continents; the origin of fjords and the primary initiation of submarine canyons; the origin of Earth’s magnetic field; the causes of geomagnetic disruptions; the source of the geothermal gradient; the origin of Earth’s petroleum and natural gas deposits; and more. The logical, causally related advances documented here stand as a reference by which to compare and evaluate the phenomenological model-nonsense that has been published for decades by government-funded scientists.